Comparison of Tumor Regression Grading of Residual Pancreatic Ductal Adenocarcinoma Following Neoadjuvant Chemotherapy Without Radiation: Would Fewer Tier-Stratification Be Favorable Toward Standardization?. (March 2019) - Kim, Sunhee S.; Ko, Andrew H.; Nakakura, Eric K.; Wang, Zhen J.; Corvera, Carlos U.; Harris, Hobart W.; Kirkwood, Kimberly S.; Hirose, Ryutaro; Tempero, Margaret A.; Kim, Grace E.
Abstract : To assess whether the College of American Pathologists (CAP) and the Evans grading systems for neoadjuvant chemotherapy without radiation-treated pancreatectomy specimens are prognostic, and if a 3-tier stratification scheme preserves data granularity. Conducted retrospective review of 32 patients with ordinary pancreatic ductal adenocarcinoma treated with neoadjuvant therapy without radiation followed by surgical resection. Final pathologic tumor category (AJCC eighth edition) was 46.9% ypT1, 34.4% ypT2, and 18.7% ypT3. Median follow-up time was 29.8 months, median disease-free survival (DFS) was 19.6 months, and median overall survival (OS) was 34.2 months. CAP score 1, 2, 3 were present in 5 (15.6%), 18 (56.3%), and 9 (28.1%) patients, respectively. Evans grade III, IIb, IIa, and I were present in 10 (31.2%), 8 (25.0%), 7 (21.9%), and 7 (21.9%) patients, respectively. OS (CAP: P =0.005; Evans: P =0.001) and DFS (CAP: P =0.003; Evans: P =0.04) were statistically significant for both CAP and Evans. Stratified CAP scores 1 and 2 versus CAP score 3 was statistically significant for both OS ( P =0.002) and DFS ( P =0.002). Stratified Evans grades I, IIa, and IIb versus Evans grade III was statistically significant for both OS ( P =0.04) and DFS ( P =0.02). CAP, Evans, and 3-tier stratification are prognostic of OS and DFS.